2016
DOI: 10.1007/s00586-016-4490-8
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac joint fusion for low back pain: a systematic review and meta-analysis

Abstract: SIJF appears to be a satisfactory procedure for alleviating pelvic girdle pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 25 publications
1
28
0
1
Order By: Relevance
“…Our findings both replicate and extend previous studies. In previously published case series [36][37][38][39], systematic reviews [40,41], a prospective multicenter clinical trial [42], and a recently published randomized clinical trial of similar design conducted in the USA [43], similar improvements in SIJ pain, self-rated limitations in activities due to pain (Oswestry Disability Index) and quality of life were observed in participants undergoing SIJF. Our study provides an additional, independent confirmation that the improvements after surgery are clinically important and statistically superior to those seen with continued conservative care.…”
Section: Discussionmentioning
confidence: 89%
“…Our findings both replicate and extend previous studies. In previously published case series [36][37][38][39], systematic reviews [40,41], a prospective multicenter clinical trial [42], and a recently published randomized clinical trial of similar design conducted in the USA [43], similar improvements in SIJ pain, self-rated limitations in activities due to pain (Oswestry Disability Index) and quality of life were observed in participants undergoing SIJF. Our study provides an additional, independent confirmation that the improvements after surgery are clinically important and statistically superior to those seen with continued conservative care.…”
Section: Discussionmentioning
confidence: 89%
“…48 The NHLBI tool has 14 items which are used in previous systematic reviews of observational studies. 49,50 Each item is assessed through a question where the possible answers are yes, no, or other (cannot determine, not applicable, or not reported). The NHLBI tool enables to score and weigh the evidence to rate the overall quality of each study as 'good', 'fair', or 'poor' indicating the validity of the findings in the respective study.…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
“…In patients who have failed conservative management in the way of nonsteroidal anti-inflammatory drugs (NSAIDs), physical therapy, pelvic belt stabilization, and in whom image guided joint injections have demonstrated a positive response, operative treatment with minimally invasive arthrodesis may be a definitive solution. Several studies have shown excellent functional outcomes and resolution of symptoms, however many of them are vendor sponsored with potential for conflicts of interest [ 2 3 7 14 19 20 21 22 ]. We hypothesize that a less invasive SIJ fusion technique may lead to favorable clinical outcomes with minimal associated surgical morbidity provided all other reasons for back pain have been adequately ruled out.…”
Section: Introductionmentioning
confidence: 99%